2011
DOI: 10.1021/cb100416j
|View full text |Cite
|
Sign up to set email alerts
|

Probing Elongating and Branching β-d-Galactosyltransferase Activities in Leishmania Parasites by Making Use of Synthetic Phosphoglycans

Abstract: Protozoan parasites of the genus Leishmania synthesize lipophosphoglycans (LPGs), phosphoglycans and proteophosphoglycans that contain phosphosaccharide repeat units of [−6)Gal(β1-4)Man(α1-OPO 3 H−]. The repeat structures are assembled by sequential addition of Manα1-OPO 3 H and β-Gal. In this study, an UDP-Gal-dependent activity was detected in L. donovani and L. major membranes using synthetic phospho-oligosaccharide fragments of lipophosphoglycan as acceptor substrates. Incubation of a microsomal preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Galactose residues inside the Golgi lumen are then added to GlcNAc by specific galactosyl transferases. These enzymes have not yet been studied in T. cruzi, but their activities have already been described in T. brucei (Pingel and Duszenko, 1992; Pingel et al ., 1999; Ramasamy and Field, 2012) and Leishmania (Sizova et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Galactose residues inside the Golgi lumen are then added to GlcNAc by specific galactosyl transferases. These enzymes have not yet been studied in T. cruzi, but their activities have already been described in T. brucei (Pingel and Duszenko, 1992; Pingel et al ., 1999; Ramasamy and Field, 2012) and Leishmania (Sizova et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2,[83][84][85][86][87][88] The authors have shown that substrate recognition strongly depends on several functional parameters: the negative charge of the phosphodiester bridge, the β-anomeric configuration of the Galp entity, and the H-bonding ability of the primary hydroxyls of both Manp and Galp residues. 89 Once again, synthetic substrates underlined the requirement for phosphodiester linkages. 89 Once again, synthetic substrates underlined the requirement for phosphodiester linkages.…”
Section: Proteophosphoglycans (Ppgs) and Secreted Acid Phosphatases (mentioning
confidence: 99%
“…All the prepared phosphoglycans contain a dec-9-enyl aglycone moiety as they were purposely designed [55] for (a) studying Leishmania biosynthetic enzymes and (b) further preparation of neoglycoconjugates, which could be tested as potential anti-leishmaniasis vaccines. The hydrophobicity of the dec-9-enyl chain has been exploited for assaying, first, the mannosylphosphate transferases [57, 58] and then the galactosyltransferases [59, 60] involved in the LPG biosynthesis in Leishmania . As for the bioconjugation, the high lability of the anomeric phosphodiester bridges in phosphoglycans was given the top priority while selecting techniques for the neoglycoconjugate preparation.…”
Section: Chemical Synthesis Of Phosphoglycans Of Leishmania Designed mentioning
confidence: 99%